Bem jurídico-penal supraindividual: novos e velhos desafios da teoria do bem jurídico - Tatiana Maria Badaro Baptista (2016)
This paper addresses the main challenges imposed to criminal dogmatic since the major role acquired in the legal debate by the new supra-individual interests present in modern criminal law. The reference to non-individual nor statal ownership of legal interests appears for the first time in the work of Birnbaum, maintaining itself as a mandatory topic of analysis throughout the evolutionary journey of the theory of legal interest. However, the processes of modernization, expansion and administrativization of criminal law were the ones that highlighted crimes against supra-individual interests. Those crimes generally resort to controversial criminal structures of abstract danger, more specifically the types of preparation and accumulation. This context led to the current time of crisis of the critical-garantist function of the legal interest, marked by uncertainty about the longevity of the theory and division of contemporary doctrine between opponents and supporters of such conception. In the scope of restoring the capacity of the legal interest theory to limit the criminalization processes, it is proposed to give up on an ideal conception of legal interest in favor of a real one, from which the category is understood, according to the principle of offensiveness, as an object of offense and not object of tutelage and, therefore, as something that could be injured. The concept of legal-criminal interest, even though it holds the Constitution as a starting point, finds its material content in personal theory of the legal interest, being defined as a reality given that serves the free development of human personality. Under a personalmonistic perspective, the supra-individual legal interests also meet essential human needs, but are also identified based on three criteria: 1) non-exclusive use; 2) unrivaled regular consumption and 3) non-conceptual distributiveness, factual or legal. The behaviors typified as abstract danger crimes against supra-individual legal interests must meet the general requirement of the ex ante possibility of non-insignificant damage, as well as the specific requirements of compliance with criminal purposes (crimes of preparation) and the real and imminent possibility of accumulation with harmful potential (crimes of accumulation).